2022
DOI: 10.1002/hsr2.887
|View full text |Cite
|
Sign up to set email alerts
|

Facial palsy as a manifestation of COVID‐19: A systematic review of cases

Abstract: Background and Aims Facial palsy is a rare complication of the COVID‐19 infection. Herein, we conducted a systematic review of all published cases of facial palsy post‐COVID‐19 infection in an attempt to educate the general population and medical practitioners regarding the likely occurrence of facial palsy in COVID‐19 patients, its detection, effective treatment plan, and prognosis of the condition. Methods We searched PubMed, Google Scholar, and Directory of Open Acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…In line with previous research (24), our ndings show that preexisting comorbidity and an increase in baseline in ammatory markers substantially impact the progression of COVID-19. This data suggests that careful observation of patients at admission and periodic re-evaluation throughout hospitalization are essential for selecting the appropriate treatment based on individual characteristics and COVID-19 severity and progression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous research (24), our ndings show that preexisting comorbidity and an increase in baseline in ammatory markers substantially impact the progression of COVID-19. This data suggests that careful observation of patients at admission and periodic re-evaluation throughout hospitalization are essential for selecting the appropriate treatment based on individual characteristics and COVID-19 severity and progression.…”
Section: Discussionsupporting
confidence: 92%
“…It is important to emphasize that in most cases; baseline tachycardia was associated with high body temperatures (fever) and tachypnea at admission. QTc interval prolongation of more than 440 ms in women and more than 460 ms in men was reported in 123 patients (21%) in group B vs. 12% (24) in group B.Except for isolated ventricular ectopic beats, no new-onset heart rhythm abnormalities were observed in any patient group. There was no signi cant bradycardia or ectopic-related clinical symptoms in any of the patients, and remdesivir could continue the full course.…”
Section: Cardiacmentioning
confidence: 88%
See 1 more Smart Citation
“…The present study found no significant difference in the sex distribution of patients with Bell’s palsy between before and during the COVID-19 pandemic. Two previous systematic reviews of recently reported cases found a slightly higher tendency for facial paralysis among males, but this difference was not significant [ 17 , 18 ]. However, in both the pre- and pandemic periods, there was no significant difference in the incidence of Bell’s palsy between males and females.…”
Section: Discussionmentioning
confidence: 89%
“…In a systematic review of facial paralysis in patients with COVID-19 from 1 December 2019 to 21 September 2021, in 49 studies involving 74 facial paralysis patients, complete paralysis was observed in one case, and most cases had moderate-to-severe facial dysfunction. Positive treatment outcomes were seen in 83.5% of patients, whereas 14.9% showed nonsignificant recovery [ 17 ]. However, studies on SARS-CoV-2-associated cranial nerve mononeuropathies or polyneuropathies yielded different results.…”
Section: Discussionmentioning
confidence: 99%